Uncovering protein prenylation in Th1 cells: novel prenylation sites and insights into statin and farnesyltransferase inhibition - Jana Koch; Alessandra Ruggia; Carina Beha; Irina Wipf; Damir Zhakparov; Patrick Westermann; Svenja Schmelzer; Anja Heider; Klemens Fröhlich; Katja Baerenfaller (BMC Biology)
Abstract Background T helper 1 (Th1) cell activation is an essential process for immune responses and is tightly regulated, including the prenylation of proteins critical for T cell function. Prenylation facilitates membrane association and protein function and, according to current consensus, is confined to C-terminal prenylation motifs. However, the full extent of the prenylated proteome, a broader understanding of prenylation sites, and the effects of inhibiting prenylation or blocking isoprenoid synthesis using statins remain incompletely understood. To address these gaps, we aimed to comprehensively identify and characterise protein prenylation in Th1 cells. Results Using a click chemistry-based enrichment approach followed by mass spectrometry in primary in vitro-differentiated Th1 cells, we identified both known and novel prenylated proteins, some of which exhibited differential prenylation during Th1 cell activation, highlighting the dynamic nature of the Th1 prenylome. Characterisation of these proteins revealed isoform-specific prenylation, novel C-terminal prenylation motifs, and a structural motif associated with internal prenylation. Furthermore, statin treatment influenced the Th1 prenylome, altering protein prenylation in a prenyltransferase-dependent manner, underscoring distinct enzymatic specificities and potential off-target effects. Conclusions Our findings confirm that prenylation plays a key role in Th1 cell function, with more proteins undergoing prenylation than previously known, some of which exhibit activation-dependent changes. The identification of non-canonical prenylation events challenges current views on prenylation, expanding the repertoire of modification sites. Together, our molecular insights into protein prenylation in Th1 cells and the effects of prenyltransferase inhibition and statin treatment have important implications for therapeutic strategies targeting immune regulation.